Overexpression of Cyclic Adenosine Monophosphate Effluent Protein MRP4 Induces an Altered Response to β-Adrenergic Stimulation in the Senescent Rat Heart. (February 2015) - Carillion, Aude; Feldman, Sarah; Jiang, Cheng; Atassi, Fabrice; Na, Na; Mougenot, Nathalie; Besse, Sophie; Hulot, Jean-Sébastien; Riou, Bruno; Amour, Julien
<x xml:space="preserve">Abstract</x> Background: In the senescent heart, the positive inotropic response to β-adrenoceptor stimulation is reduced, partly by dysregulation of β1- and β3-adrenoceptors. The multidrug resistance protein 4 (MRP4) takes part in the control of intracellular cyclic adenosine monophosphate concentration by controlling its efflux but the role of MRP4 in the β-adrenergic dysfunction of the senescent heart remains unknown. Methods: The β-adrenergic responses to isoproterenol were investigated in vivo (stress echocardiography) and in vitro (isolated cardiomyocyte by Ionoptix® with sarcomere shortening and calcium transient) in young (3 months old) and senescent (24 months old) rats pretreated or not with MK571, a specific MRP4 inhibitor. MRP4 was quantified in left ventricular homogenates by Western blotting. Data are mean ± SD expressed as percent of baseline value. Results: The positive inotropic effect of isoproterenol was reduced in senescent rats in vivo (left ventricular shortening fraction 120 ± 16% vs. 158 ± 20%, P < 0.001, n = 16 rats) and in vitro (sarcomere shortening 129 ± 37% vs. 148 ± 35%, P = 0.004, n = 41 or 43 cells) as compared to young rats. MRP4 expression increased 3.6-fold in senescent compared to young rat myocardium (P = 0.012, n = 8 rats per group). In senescent rats, inhibition of MRP4 by MK571 restored the positive inotropic effect of isoproterenol in vivo (143 ± 11%, n = 8 rats). In vitro in senescent cardiomyocytes pretreated with MK571, both sarcomere shortening (161 ± 45% vs. 129 ± 37%, P = 0.007, n = 41 cells per group) and calcium transient amplitude (132 ± 25% vs. 113 ± 27%, P = 0.007) increased significantly. Conclusion: MRP4 overexpression contributes to the reduction of the positive inotropic response to β-adrenoceptor stimulation in the senescent heart.